The association between serum 25-hydroxyvitamin D levels and retinopathy of prematurity in preterm infants - Xiangyun Yin; Shimin Xu; Xuefei Zhang; Liangliang Li; Hongmin Xi; Lili Ma; Mengya Sun; Ping Yang; Xianghong Li; Hong Jiang (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to investigate the correlation between serum 25-hydroxyvitamin D (25(OH)D) levels and retinopathy of prematurity (ROP) in premature infants one month after birth.MethodsPreterm infants (gestational age <32 weeks) admitted to the Affiliated Hospital of Qingdao University from 2017 to 2022 were divided into ROP and non-ROP groups based on ROP occurrence any stage. Serum 25(OH)D levels and clinical data were compared between the two groups at 1 month after birth, and the relationship between vitamin D levels and ROP was analyzed.ResultsAmong the 217 premature infants included, 55 (25.35%) were in the ROP group, and 162 (74.65%) were in the non-ROP group. The ROP group had lower gestational age and birth weight, longer invasive ventilation (IV), non-invasive ventilation (NIV), and oxygen therapy times compared to the non-ROP group. Apgar scores, cesarean delivery, and antenatal steroids ratios were lower in the ROP group, while sepsis and pulmonary surfactant utilization ratios were higher (all p < 0.05). Significant differences in serum 25-(OH)D levels were observed among children in the non-ROP group (14.20 ± 5.07 ng/ml), ROP treated group (7.891 ± 1.878 ng/ml), and untreated group (12.168 ± 4.354 ng/ml) (p < 0.001). Multivariate regression analysis identified antenatal steroids as protective factors and lower birth weight, serum 25-(OH)D levels, long-term invasive mechanical ventilation, and sepsis as independent risk factors for ROP in premature infants.ConclusionVitamin D, lower birth weight, long-term invasive mechanical ventilation, and sepsis were associated with incidence of ROP in preterm infants. Vitamin D was associated with the severity of ROP, emphasizing the importance of prudent vitamin D supplementation and regular monitoring of serum 25-(OH)D levels.